Effect of Milk Replacer on Growth Performance and Economics of Raising Preweaned HF Crossbred Calves - Jadav, Prabhatsinh V.; Gaur, Vinay (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
As compared to whole milk feeding, milk replacer is an excellent cheaper source of nutrition for calves prior to weaning. For this study, 20 newborn HF crossbred calves were divided into two equal groups each of 10 animals and were put under 8 weeks feeding trial. The calves of control group (T1) were fed cow’s whole milk as per owner’s practice in the field, while those of treatment group (T2) were fed whole milk @ 2.5 ltr during 1st week and then milk replacer (Amul brand) was fed @ 50 gm and 150 gm along with 2.0 ltr and 1.0 ltr whole milk during 2nd and 3rd week, respectively, and then only the milk replacer @ 250, 350, 450, 500 and 400 gm was used during 4th, 5th, 6th, 7th and 8th week, respectively. Weekly body weight was calculated based on measurements of heart girth and body length using Shaffer’s formula. The average body weight during 1st week of age was statistically similar in both groups. The overall mean values of gain in body weight and daily gain in weight in control and treatment groups were 20.40±0.51 vs. 24.67±0.41 kg, and 364.29±9.04 vs. 440.54±7.32 g (20.09% and 20.92% increase in T2 over T1), respectively. The weekly growth rate and overall daily gain in body weight in calves of T2 group were significantly (p
Keywords: Body Weight; Gain in body weight; HF crossbred calves; Milk replacer; Whole milk